The final thesis – learning outcome of professional bachelor - Jukonienė, Birutė; Gudaitienė, Ona; Sinevičienė, Melanija (Buhalterinės apskaitos teorija ir praktika, 2013)
The article examines the procedure and issues of preparation, defence and assessment of graduation papers of students majoring in accounting at the Faculty of Economy of Vilnius College. A graduation paper – a generalization of all study results on which basis the author is awarded a professional bachelor’s degree – is the most important form of student’s independent work that discloses his/her preparedness for work. While preparing and defending a graduation paper, graduates have a possibility to demonstrate the knowledge acquired as well as practical skills. The graduation paper analyses theoretical and practical aspects of the formation and implementation of an accounting policy in a business company; provides conclusions and suggestions for future perspectives. After examining and analysing the preparation and assessment of graduate papers in the accounting study programme at the Faculty of Economics of Vilnius College, it may be claimed that the most popular topics of graduation papers in 2013 were as follows: preparation of a set of financial statements and analysis of indicators; accounting and analysis of fixed tangible assets; accounting and analysis of income. The defence of graduation papers is a public procedure and takes place in a sitting-meeting of a Qualifying Commission appointed by order of the Director of Vilnius College and is assessed in conformity with the procedure laid down in the methodological instructions for study works. Reviewers and the Qualifying Commission evaluated the majority of graduation papers as “excellent” and “good”. In terms of the competences achieved it may be claimed that 92 percent of all the graduation papers were evaluated at the highest (9-10 points) and average (7-8 points) level.